Introduction: Building resilient African food systems after COVID-19 - Ulimwengu, John M.; Constas, M.A.; Ubalijoro, É.; Collins, J. (AKADEMIYA2063, 2021)
The COVID-19 pandemic has quickly spread across the world over the last two years, causing a significant number of deaths—more than 4.55 million as of October 2021—and hospitalizations as well as economic disruption. This global crisis has triggered a transformation toward a new, elusive “normal that may take years to fully materialize despite the amazingly fast discovery and deployment of vaccines, and more recently, the progress of COVID-19 treatments in clinical trials. The World Health Organization established a global target of 10 percent vaccination by the end of September 2021; although many developed countries have fully vaccinated 50–75 percent of their populations, African vaccination rates have only reached 4.4 percent (Mwai 2021).